2022
DOI: 10.3390/biomedicines10081965
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Cortical Electrical Stimulation during the Acute Stage of Traumatic Brain Injury Improves Functional Recovery

Abstract: Functional restoration is an important issue in the treatment of traumatic brain injury (TBI). Various electrical stimulation devices and protocols have been applied in preclinical studies and have shown therapeutic potential for brain trauma. Short-term invasive cortical electrical stimulation during the acute stage of TBI might be a feasible adjuvant therapy for patients with moderate-to-severe brain injury receiving neurosurgical treatment in the intensive care unit. However, the therapeutic effects of shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 68 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…There is growing evidence to show that a significant fraction of subthreshold or background Na + currents is functionally active in varying types of excitable cells [ 20 , 22 , 24 , 27 , 57 , 58 , 59 , 60 , 61 ]. Recent investigations have also demonstrated possible modifications of sinusoidal voltage wave on membrane ionic currents [ 62 , 63 , 64 , 65 ]. For these reasons, efforts were further given to answer the question of whether I Na(P) can be susceptible to adjustments by sinusoidal voltage waveform or whether or how sinusoidal voltage-induced I Na(P) can be perturbed by adding KB-R7943.…”
Section: Resultsmentioning
confidence: 99%
“…There is growing evidence to show that a significant fraction of subthreshold or background Na + currents is functionally active in varying types of excitable cells [ 20 , 22 , 24 , 27 , 57 , 58 , 59 , 60 , 61 ]. Recent investigations have also demonstrated possible modifications of sinusoidal voltage wave on membrane ionic currents [ 62 , 63 , 64 , 65 ]. For these reasons, efforts were further given to answer the question of whether I Na(P) can be susceptible to adjustments by sinusoidal voltage waveform or whether or how sinusoidal voltage-induced I Na(P) can be perturbed by adding KB-R7943.…”
Section: Resultsmentioning
confidence: 99%
“…Yoon et al9 reported significant improvement in motor control in rats with moderate to severe TBI but no major effects in coordination or balance. However, other animal studies have demonstrated that TBI treated with MCS confers marked improvement in spatial memory, sensorimotor function, and motor coordination 1,10,11. These studies did not use the same behavioral tests to quantify motor abilities but demonstrated that cortical stimulation promotes motor recovery after TBI.…”
Section: Preclinical Studies In Animal Modelsmentioning
confidence: 99%
“…However, other animal studies have demonstrated that TBI treated with MCS confers marked improvement in spatial memory, sensorimotor function, and motor coordination. 1,10,11 These studies did not use the same behavioral tests to quantify motor abilities but demonstrated that cortical stimulation promotes motor recovery after TBI. It would be beneficial to obtain more consistent data if there was consensus on which tests more accurately measure functional recovery.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…The use of electrical brain stimulation (EBS) as a therapeutic modality for treatment of brain disorders has evolved significantly, with recent developments pushing pathway activation, etc., to treat Parkinson's disease (PD), Alzheimer's disease (AD), and other central nervous system (CNS) disorders. [6][7][8][9][10][11][12][13][14] Take treatment for AD as an example, studies have suggested that the use of 40 Hz flicker stimulation can modulate abnormal gamma oscillations in the brain waves of AD model mice to some extent, thereby improving impaired learning and memory functions. [15][16][17] However, the latest research refutes this finding, claiming that flicker stimulation cannot regulate gamma oscillations in brain waves, nor can it reduce excessive Aβ deposition in the brains of AD mice or ameliorate AD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The use of electrical brain stimulation (EBS) as a therapeutic modality for treatment of brain disorders has evolved significantly, with recent developments pushing the boundaries of our understanding and treatment capabilities 1–6 . The principle of this approach is to use precisely applied electrical currents to modulate neuronal activity, such as neuronal membrane stability and action potential, ion and neurotransmitter fluxes, intracellular pathway activation, etc., to treat Parkinson's disease (PD), Alzheimer's disease (AD), and other central nervous system (CNS) disorders 6–14 …”
Section: Introductionmentioning
confidence: 99%